Gambaran Kejadian Miopia pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi - Sambulele, Ananda P.; Najoan, Imelda H. M.; Supit, Wenny P. (Medical Scope Journal, 2025)
Abstract: Myopia is a condition in which incoming light is focused in front of the retina, causing distant objects to appear blurred. The prevalence of myopia is increasing rapidly and becoming a challenge to quality of life. Myopia is on the rise not only in children, but also in young adults. If left untreated, it can lead to serious complications and even blindness. This study aimed to determine the incidence of myopia among students of the Faculty of Medicine, Universitas Sam Ratulangi. This was a quantitative and descriptive study using a cross-sectional design. Subjects were students of the Faculty of Medicine, Universitas Sam Ratulangi who suffered from myopia taken by purposive sampling technique. The results showed that 31 students suffered from myopia, of which 26 students (83.9%) had low myopia. Myopia was more prevalent in the age group of 21 years with 13 students (41.9%), and in females with 24 students (77.4%). Myopia was found to be high in students with a family history of myopia with 17 students (56.4%). In conclusion, the highest incidence of myopia is found in individuals with low myopia, female, 21 years of age, and a family history of myopia. Keywords: myopia; degree of myopia; age; sex; family history   Abstrak: Miopia adalah suatu kelainan dimana cahaya yang masuk ke mata difokuskan di depan retina sehingga objek yang jauh terlihat buram. Prevalensi miopia mengalami peningkatan pesat baik pada anak maupun dewasa yang menjadi tantangan bagi kualitas hidup masyarakat. Jika tidak tangani, myopia dapat menyebabkan komplikasi serius bahkan kebutaan. Penelitian ini bertujuan untuk mengetahui gambaran kejadian miopia pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah deskriptif kuantitatif dengan desain potong lintang. Subjek penelitian ialah mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi yang menderita miopa diambil dengan teknik purposive sampling. Hasil penelitian ini menunjukkan jumlah subjek yang menderita miopia ialah 31 mahasiswa; 26 mahasiswa (83,9%) memiliki derajat ringan. Miopia lebih banyak terjadi pada usia 21 tahun dengan jumlah 13 mahasiswa (41,9%). Kejadian miopia ditemukan paling banyak pada perempuan sebanyak 24 mahasiswa (77,4%). Kejadian miopia ditemukan tinggi pada mahasiswa dengan riwayat keluarga miopia, yakni 17 mahasiswa (56,4%). Simpulan penelitian ini ialah kejadian miopia tertinggi didapatkan pada miopia derajat ringan, jenis kelamin perempuan, usia 21 tahun, dan memiliki riwayat keluarga dengan miopia. Kata kunci: miopia; derajat miopia; usia; jenis kelamin; riwayat keluarga